Laparoscopic cholecystectomy: an experience of university hospital in eastern Nepal (Health Renaissance, 2012)
Introduction: Laparoscopic cholecystectomy has become the standard treatment for symptomatic gall stones disease. Objective of this study to assess the safety of this procedure, to audit the conversion and bile duct injury rates and the factors which influence these. Methods: A total of 346 laparoscopic cholecystectomy over a six months period (15 April 2010 to 14 October 2010) with their demographics and ethnic group, conversion to open operation and bile duct injury were recorded. Pre operative, operative and the relevant data were collected prospectively. A chi squire test was done to determine significance of any differences between subgroups. Results: Male to female ratio was 1:4. The most common indication for surgery was biliary colic/dyspepsia (51%),cholecystitis (chronic- 49.4%, acute- 12%), pancreatitis, gallbladder polyp, history of recurrent attacks 16.5%,obesity 19.1%. 128 were operated by consultant, 170 by junior consultants, 48 were by senior residents. There was no statistically significant difference found in the duration of surgery between consultants and junior consultants (P=0.264), however significance between consultants and senior residents (P=